A Comparative Study of Proliferative Nodules and Lethal Melanomas in Congenital Nevi From Children. (March 2015) - Yélamos, Oriol; Arva, Nicoleta C.; Obregon, Roxana; Yazdan, Pedram; Wagner, Annette; Guitart, Joan; Gerami, Pedram
Abstract : Differentiating proliferative nodules (PNs) from melanomas arising in congenital nevi (CN) is a considerable challenge for dermatopathologists. Most of the specimens dermatopathologists assess that deal with this differential diagnosis involve proliferations of melanocytes arising in the dermis. In this study, we compare the clinical, histologic, and molecular findings of these 2 conditions. In our database, we found 22 examples of PNs arising in the dermis of CN and 2 cases of lethal melanomas arising from the dermis/epidermis of CN of children. Importantly, we found that among dermal melanocytic proliferations arising from CN in children, PNs are far more common than lethal melanomas. Clinically, multiplicity of lesions favored a diagnosis of PNs, whereas ulceration was infrequent in PNs compared with lethal melanomas. Histologically, PNs showed several distinct patterns including expansile nodules of epithelioid melanocytes with mitotic counts lower than that seen in the melanomas (1.67 vs. 12.5 mitoses/mm 2 ), a small round blue cell pattern often highly mitotically active, neurocristic-like, blue nevus-like, a nevoid melanoma-like pattern, or an undifferentiated spindle cell pattern. The lethal melanomas both featured expansile nodules of epithelioid melanocytes with high mitotic counts (range, 5 to 20 mitoses/mm 2 ) and an ulcerated overlying epidermis. At the molecular level, the PNs showed mostly whole chromosomal copy number aberrations, which in some cases were accompanied by rare partial chromosomal aberrations, whereas both lethal melanomas showed highly elevated copy number aberrations involving 6p25 without gains of the long arm of chromosome 6.